2020
DOI: 10.3390/antibiotics9070391
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Spectrum of Titroleane™: A New Potent Anti-Infective Agent

Abstract: Tea Tree oil (TTO) is well known for its numerous good properties but might be also irritating or toxic when used topically or ingested, thus limiting the number of possible applications in Humans. The aim of the study was to characterize the antimicrobial spectrum as well as the toxicity of Titroleane™, a new anti-infective agent obtained from TTO but cleared of its toxic monoterpenes part. The susceptibility to Titroleane™ of various pathogens (bacteria and fungi) encountered in animal and human heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 72 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…It was previously shown that a commercial fraction of TTO named Titroleane™ exhibits a similar antimicrobial activity to TTO, although it was depleted from its monoterpenes which were expected to be the most important antimicrobial molecules in TTO [ 7 ]. We investigated the role of some major compounds of Titroleane™ to maintain the antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was previously shown that a commercial fraction of TTO named Titroleane™ exhibits a similar antimicrobial activity to TTO, although it was depleted from its monoterpenes which were expected to be the most important antimicrobial molecules in TTO [ 7 ]. We investigated the role of some major compounds of Titroleane™ to maintain the antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes results of MICs for terpinen-4-ol and α-terpineol in % (v:v), mM and mg/mL. As percentage as a concentration unit is commonly used for essential oils and their compounds, this unit is used in the rest of the article [ 7 , 15 , 17 , 18 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it was thought that the antimicrobial effect was due to this substance. Johansen et al (2020) also investigated the antimicrobial activity of tea tree essential oil against C. difficile and C. sporogenes. When the results were compared with those of Johansen et al's study, although the percentages of the active ingredients 4terpineol and Ɣ-terpinene were similar, they determined lower MIC values than our values.…”
Section: Resultsmentioning
confidence: 99%